Problematic aspects of management accounting for operating costs - Ya.F. Averkyn (Економіка, управління та адміністрування)
Management accounting depends on the problem of accounting policy development in terms of rapid adaptation to modern management concepts, which also contribute to the deepening of the theory and development of management practice and accounting. The urgency of the problem is explained by the fact that the formation of accounting policy in its current form, creates the illusion of making changes in management for business owners and managers, although it only slightly streamlines the traditional accounting system and does not provide any necessary decisions and changes. There is a substitution of concepts, and this diverts attention from the current problems of development of the management system in its broadest sense, as well as management accounting. Therefore, there is a need to form a block of accounting problems as part of the overall long-term program of management system development, in which accounting policy issues will be inextricably linked with the organization of management accounting. In this regard, the author outlines the purpose of the article in terms of studying the problematic aspects of management accounting of operating costs of the brewing industry. The article reveals the features of management accounting of operating costs of enterprises in the brewing industry. The author emphasizes the need to focus on the process of cost management, compliance with the rules of the technological process, avoiding unproductive loss of resources, reducing the level of waste, which will help ensure the objectivity of the process of financial results. The article presents the author's algorithm for assigning overhead costs to accounts 23 and 90. The author proposes to disaggregate the itemj of calculating the costs of salaries for the basic salary and additional salary, especially for PJSC «Slavutych Brewery», as the cost elements «Labor costs» at this company are 27–34 %. The author considers, it would be reasonable to detail other direct costs in the costing items to understand their share in the cost structure of operating activities.